Private equity buyouts & firm exporting in crisis periods: Exploring a new channel - Paul Lavery; Marina-Eliza Spaliara; Holger Görg (Journal of Corporate Finance, 2024)
This paper examines whether private equity (PE)-backed companies are better able to remain active on export markets compared to similar non-PE firms, when hit by a negative shock. We look at two such recent shocks, namely the global financial crisis (GFC) and COVID-19 pandemic. We construct two matched samples, one for each crisis period, to assess the resilience of exporting under PE ownership in recessionary periods. We then explore how improvements in working capital management allow PE-backed firms to engage in international activities and maintain their export relationships relative to similar, non-PE-backed firms. Our results show that the export activities of PE-backed firms are significantly more resilient to the effects of the GFC but less pronounced following COVID-19. PE investment enhances working capital management, which in turn improves the persistence in export markets at the onset of the crises.
Keywords: F14; G01; G32; G34; 330; Private equity buyouts; exporting; working capital; recessions